2022
DOI: 10.21203/rs.3.rs-1219965/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bolder Conservation Future for Indonesia: Conserving Biodiversity, Carbon And Unique Ecosystem In Sulawesi

Abstract: As more ambitious protected area (PA) targets for the post-2020 global biodiversity framework is set beyond Aichi Target 11, new spatial prioritisation thinking is required to expand protected areas to maximise different environmental values. Our study focuses on the biodiversity and forest-rich Indonesian island of Sulawesi, which has a terrestrial PA network that covers 10% of the island. We run scenarios to identified areas outside the current PA network and their representativeness of conservation features… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to Riggs et al (2021), the entire landscape reached 84,726 Ha, including the area of production forest, protected forest, and small-scale plantation. Meanwhile, Pusparini et al (2022) stated that the total area of this landscape could reach 1.29 million Ha and form a corridor that connects two nearby protected forest areas and two KBAs. Pusparini et al (2022) found that this landscape is consistently identified as one of the highest prioritized areas for protection in various scenarios in the model that has been made.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…According to Riggs et al (2021), the entire landscape reached 84,726 Ha, including the area of production forest, protected forest, and small-scale plantation. Meanwhile, Pusparini et al (2022) stated that the total area of this landscape could reach 1.29 million Ha and form a corridor that connects two nearby protected forest areas and two KBAs. Pusparini et al (2022) found that this landscape is consistently identified as one of the highest prioritized areas for protection in various scenarios in the model that has been made.…”
Section: Study Sitementioning
confidence: 99%
“…Meanwhile, Pusparini et al (2022) stated that the total area of this landscape could reach 1.29 million Ha and form a corridor that connects two nearby protected forest areas and two KBAs. Pusparini et al (2022) found that this landscape is consistently identified as one of the highest prioritized areas for protection in various scenarios in the model that has been made. This research was conducted in Mekarti Jaya Village in Puhowato District, Gorontalo Province, Indonesia directly adjacent to this landscape.…”
Section: Study Sitementioning
confidence: 99%
“…Temperature ranges from 22 0 C to 32 0 C, and humidity can reach 100% on many months. The topography varies from mild slope into mountainous height; hence it covers coastal forest, lowland forest, montane forest, and moss forest where Anaphalis javanica and Nepenthes maxima can still be found [8,9].…”
Section: Introductionmentioning
confidence: 99%